Measurement of the Forward-Backward Charge Asymmetry and Extraction of sin(2)theta(eff)(W) in pp -> Z/gamma(*)+X -> e(+)e(-)+X Events Produced at s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Rangel, M. S.; et al. (Amer Physical Soc, 2008)
We present a measurement of the forward-backward charge asymmetry (A(FB)) in pp -> Z/gamma(*)+X -> e(+)e(-)+X events at a center-of-mass energy of 1.96 TeV using 1.1 fb(-1) of data collected with the D0 detector at the Fermilab Tevatron collider. A(FB) is measured as a function of the invariant mass of the electron-positron pair, and found to be consistent with the standard model prediction. We use the A(FB) measurement to extract the effective weak mixing angle sin(2)theta(eff)(W)=0.2326 +/- 0.0018(stat)+/- 0.0006(syst).